APPROACH TO ESTIMATION OF THE MARKET VOLUME FOR COMPANIES OPERATING IN THE B2B SEGMENT - Alla B. Kochergina (Статистика и экономика)
This article shows the approach for estimating amount of alive enterprises inRussia. The main focus is on the way of detecting an business-active companiesusing the formal signs. The author proposes some signs for indicating of thebusiness activity. The developed model allows to clarify the amount of active enterprises in stages using those signs. The author provides the approach how to applythis model for different markets.